PENGARUH INDEPENDENSI, KOMPETENSI, PENGALAMAN, DAN PENDIDIKAN TERHADAP PROFESIONALISME AUDITOR (Studi Empiris pada Auditor BPKP Perwakilan Provinsi Riau) - Toruan, Jupri Lumban; -, Hardi; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
There are some factors influencing the auditors’ professionalism, and it does be reason why this studies important. This study attempts to see the influence of independency, competency, experience and , education to auditor professionalism, especially those who are working in BPKP Riau.The population of study is all auditors who worked on the BPKP Riau. Methods of data collection in this study is the method of questionnaire survey using instruments that are delivered directly to the BPKP Representative Riau Province. The Respondents are used in the analysis were 47 respondents ( 85 % ) Methods of Analysis is conducted with a multiple regression analysis using SPSS (Statistical Product and Service Solutions )Version 17.The results of testing that has been done.Partial regression test (t test) showed that the auditors’ independency, competency, experience had a influences significantly and positively towards auditor professionalism, while auditor education have no effect significantly on their professionalism.The coefficient of determination in this study was65,7 % .These four variables affect the dependent variable was 65,7 % , while 34,3 % is influenced by other variables that are not addressed in this study . Keywords: independency,competency,experience,education,and professionalism